Progressive and Perfective Local Wisdom of Civil Law Study - Japansen Sinaga; Irene Puteri AS Sinaga; Alum Simbolon (Warmadewa Press, 2024)
Local wisdom, reflecting the values, knowledge, and strategies of local communities, plays a crucial role in shaping Indonesia's cultural identity and societal resilience. With its vast diversity, each region of Indonesia possesses unique traditions and local wisdom, integral to the nation's heritage. However, modernization and external influences have gradually eroded these traditional practices, particularly among younger generations. This study explores the role of local wisdom in Indonesia’s customary law and its integration into civil law using normative research methods, analyzing laws, doctrines, and jurisprudence. The research aims to identify the impact of local wisdom on customary law development and examine how progressive and responsive local wisdom can be effectively applied within the civil law framework. Findings suggest that integrating local wisdom into the legal system can create a more inclusive, adaptive, and contextually relevant framework, contributing significantly to the development of civil law theory and practice in Indonesia.